2018
DOI: 10.1097/pec.0000000000001647
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents of Discharged Pediatric Emergency Department Patients Read Discharge Instructions?

Abstract: Objectives: The percentage of discharged emergency department (ED) patients who read discharge instructions (DCIs) is unknown. In this study of parents of pediatric ED patients, we attempt to quantify the DCI readership rate and identify variables associated with readership. We hypothesized that few families would read their child's DCIs. Methods:We conducted a prospective, randomized study of parents of pediatric patients who were discharged home from the ED. We randomized participants to receive a study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The most common formats are verbal, written, and video instructions. One of the disadvantages of verbal instructions is that information can be incomplete and that in this case comprehension depends mostly on the healthcare provider communication skills [9,10]. Instead, written instructions are frequently left unread by caregivers [9] and mostly overestimate the caregivers' health literacy level [10].…”
Section: Introductionmentioning
confidence: 99%
“…The most common formats are verbal, written, and video instructions. One of the disadvantages of verbal instructions is that information can be incomplete and that in this case comprehension depends mostly on the healthcare provider communication skills [9,10]. Instead, written instructions are frequently left unread by caregivers [9] and mostly overestimate the caregivers' health literacy level [10].…”
Section: Introductionmentioning
confidence: 99%
“…13 As previous research has shown, only a minority of pediatric patients' parents read discharge instructions after visiting the ED; therefore, it is unlikely that pediatric patients themselves are inclined to read text-only discharge instructions at baseline, much less after a head injury. 30 However, a feasibility study of a comicbased ED discharge instruction for children on pain management reported that the printed comics were well liked by pediatric patients, were easy-to-read in a short period, and also improved parents' recall of key teaching points related to pain management. 19 Although both the comic and video were rated favorably, patients who viewed both interventions rated the video more highly than the comic.…”
Section: Discussionmentioning
confidence: 99%
“…Comic-based materials, which combine pictures with small amounts of text, can enhance understanding, improve connections between new and old knowledge, and improve recall, which may make comic-based materials easier to interpret and learn from after a concussion or traumatic brain injury 13 . As previous research has shown, only a minority of pediatric patients' parents read discharge instructions after visiting the ED; therefore, it is unlikely that pediatric patients themselves are inclined to read text-only discharge instructions at baseline, much less after a head injury 30 . However, a feasibility study of a comic-based ED discharge instruction for children on pain management reported that the printed comics were well liked by pediatric patients, were easy-to-read in a short period, and also improved parents' recall of key teaching points related to pain management 19 …”
Section: Discussionmentioning
confidence: 99%
“…Although this was not formally tested postdischarge, a more likely possibility is that there may have been greater retention of information in the video group. There is ample evidence that written discharge instructions are often poorly understood or altogether not read . Retention of knowledge has been found to be greater with verbal reinforcement of written discharge instructions, and the video used both verbal and written communication.…”
Section: Discussionmentioning
confidence: 99%
“…Survey data suggest high levels of parental uncertainty regarding the treatment of AOM . Moreover, less than 30% of U.S. parents with children with AOM receive instructions on pain management, and only a minority of parents report reading discharge instructions . It has become abundantly clear there is an urgent need to improve the delivery of discharge instructions for AOM.…”
mentioning
confidence: 99%